OVERVIEW OF IOT ON REMOTE PATIENT FOR MONITORING AND SMART MEDICAL DEVICES - Bashiru, Aliyu Sani; Badamasi, H.; Bashar, A. (FUDMA Journal of Sciences, 2025)
The advantage of (IoT) technologies in the healthcare sector represents a transformative shift with huge significant important. This paper provides a sight on adoption of IoT in healthcare, focusing on specific sensor types used in treatment of remote patients. It underscores successful real-world applications, including remote patient monitoring, individualized treatment strategies, and streamlined healthcare service delivery. However, it will state the challenges been encounter for the full potential of IoT in healthcare sector. This includes challenges, benefit and future potential ensuring seamless interoperability, and optimizing the use of IoT in healthcare sector. This paper will courage to inspire practitioners and researchers by highlighting the practical implications of IoT in healthcare and enhance overall healthcare efficiency, patient care, resource allocation and provide atmospheric communication environment in health sector.